2023
DOI: 10.1007/s00431-022-04761-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and risk factors of plastic bronchitis caused by refractory Mycoplasma pneumoniae pneumonia in children: a practical nomogram prediction model

Abstract: Early assessment of refractory Mycoplasma pneumoniae pneumonia (RMPP) with plastic bronchitis (PB) allows timely removal of casts using fiberoptic bronchoscopic manipulation, which relieves airway obstruction and limit sequelae development. This study aimed to analyze clinical data for risk factors and develop a nomogram for early predictive evaluation of RMPP with PB. The clinical data of 1-14 year-old patients with RMPP were retrospectively analyzed. Patients were classified into a PB or non-PB group. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The remaining individuals achieved recovery. Yang L et al [ 10 ] PB 133 February 2019 to January 2020 and August 2021 to July 2022 6.70 ± 2.49 years old Male/Female ratio of 71:62 NA NA Clinical conditions improved Zhang H et al [ 11 ] PB 52 January 2015 to December 2019 5.69(range, 4.89–6.48) years old Male/Female ratio of 25/27 10.44 ± 2.94 Macrolide, Methylprednisolone Six cases progressed to bronchiolitis obliterans, while the remaining individuals achieved recovery. Zhang T et al [ 12 ] PB 3 March, 2016 1.9 years old Female 9 Cephalothin, Azithromycin, Methylprednisolone Recovery October, 2015 2.4 years old Female 8 Cephalothin, Azithromycin, Methylprednisolone, Gamma globulin Recovery April, 2016 4.3 years old Male 7 Cephalothin, Azithromycin, Methylprednisolone, Gamma globulin Recovery …”
Section: Discussionmentioning
confidence: 99%
“…The remaining individuals achieved recovery. Yang L et al [ 10 ] PB 133 February 2019 to January 2020 and August 2021 to July 2022 6.70 ± 2.49 years old Male/Female ratio of 71:62 NA NA Clinical conditions improved Zhang H et al [ 11 ] PB 52 January 2015 to December 2019 5.69(range, 4.89–6.48) years old Male/Female ratio of 25/27 10.44 ± 2.94 Macrolide, Methylprednisolone Six cases progressed to bronchiolitis obliterans, while the remaining individuals achieved recovery. Zhang T et al [ 12 ] PB 3 March, 2016 1.9 years old Female 9 Cephalothin, Azithromycin, Methylprednisolone Recovery October, 2015 2.4 years old Female 8 Cephalothin, Azithromycin, Methylprednisolone, Gamma globulin Recovery April, 2016 4.3 years old Male 7 Cephalothin, Azithromycin, Methylprednisolone, Gamma globulin Recovery …”
Section: Discussionmentioning
confidence: 99%
“…We develop a nomogram model to predict SMPP in children and to evaluate using multiple aspects such as imaging, bronchoscopy, condition scoring, and inflammatory indicators. Zhang’s RMPP plastic bronchitis nomogram prediction model is mainly based on clinical manifestations such as fever, extrapulmonary complications, pleural effusion, cough duration, and lactate dehydrogenase [ 23 ]. Zhao et al mainly used laboratory indicators such as peak body temperature, neutrophil ratio, platelet count, interleukin-6, lactate dehydrogenase, and atelectasis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LDH is also often used as a predictor of severe pneumonia. 18 , 19 A retrospective analysis of NP by Li et al 11 found that CRP is an independent predictor of the degree of lung necrosis. CRP > 48.35 mg/L had a high predictive value for the diagnosis of NP, according to Qian et al 7 Zhou et al 20 found that WBC and CRP in the NP group caused by Mycoplasma pneumoniae were significantly higher than those in non-NP group.…”
Section: Discussionmentioning
confidence: 99%